EVALUASI PROGRAM SKB (SANGGAR KEGIATAN BELAJAR) KABUPATEN KAMPAR DALAM MENANGGULANGI PENDIDIKAN ANAK PUTUS SEKOLAH - Jusmareni Jusmareni; Zulfan Saam; Almasdi Syahza (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2018)
This study aims to uncover, analyze and evaluate the program SKB ( SKB ) intackling the education of children dropping out of school in the district of Kampar. This studyused a qualitative approach. Data collection is done by observation, interview and documentation.Examination of data validity was tested the validity of the form of triangulation and memberchecking. Evaluation model used is the model CIPP. From the results of this study indicate thatthe Program Implementation for SKB Kampar in tackling the education of school children fromthe evaluation components of context, input, process and products are in both categories becauseof the four components in the evaluation of only one component of which is the unfavorablecategory namely the process component. Implementation of the program SKB Kampar districtis very helpful in minimizing the number of dropouts in Kampar regency. Evaluation programfor SKB in this penelititan Packet focuses on program C. Residents learned in Package C is thecitizens who already have a junior high school diploma and diploma Package B. All officials arealready earning has taught appropriate educational background, mastery of officials in thepresentation of the material based on competence, In the curriculum that need improvementeducation calendar. Means of support for the implementation of the existing program despiteinadequate. Financing for SKB comes from Kampar District Government and some of thelearners. In the process of the most important components that must be considered are theobstacles encountered in the implementation of the program should be addressed as soon aspossible.